Performance Assessment and Comparison of Two Types Linear Motors for Electromagnetic Catapult - Huilai Li; Xiaomin Li; Zhiyuan Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Linear motors are strong candidates in electromagnetic launching technology for space-use. In this paper, two types linear motors, including parallel magnetic circuit linear permanent magnet brushless DC motor (PMC-LPMBDCM) and serial magnetic circuit linear permanent magnet brushless DC motor(SMC-LPMBDCM), have been presented for electromagnetic catapult. The rudimental configurations of these two-type of linear motors are researched respectively. Then the contrast of performance between PMC-LPMBDCM and SMC-LPMBDCM is investigated detailedly. The electromagnetic properties and thrust characteristics are researched by finite element analysis(FEA) and experiment. Simulated and measured results can provide useful references to select the suitable type of motor for electromagnetic catapult. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4027